Varietal screening and inheritance of resistance to brown spot disease in rice (Oryza sativa) - PRASAD, K; SHUKLA, V D; SINHA, P K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted to identify the new resistant varieties of diverse origin and inheritance of genes controlling brown spot disease. Rice (Oryza sativa L.) varieties (560) from diverse sources were screened during wet seasons of 1990 and 1991 for brown spot (Cochilobolus miyabeanus Ito & Kuribayashi) disease in the field under natural infection where high disease pressure was created by cultural operations. Twenty-two varieties were identified to be resistant to this disease. The inheritance of resistance was studied during 1992-94 in 6 crosses involving 3 resistant parents and 1 susceptible parent. It was found that resistance to brown spot disease was controlled by 2 pairs of recessive genes. The 3 resistant parents ’RR 35-4-1’,’RR 20-5’ and ’RR 36-141 ’ had single recessive gene in each. Gene present in ’RR 20-5’ and ’RR 36-141’ was the same whereas gene present in ’RR 35-4-1’ was different from other 2 resistant parents.